PENGARUH PEMBINAAN ASATIDZ TERHADAP AKHLAK SISWA DI SEKOLAH DASAR NEGERI 1 KECAMATAN DARANGDAN KABUPATEN PURWAKARTA - Fachriyah, Neng Vera; Nasir, Tatang Muh; Hudah, Iana Rotul; Oding, Oding; Jumiati, Menia (Attadib: Journal of Elementary Education, 2023)
This research was conducted at Sekolah Dasar Negeri 1 Putri Islamic Boarding School, Kec. Darangdan district. Purwakarta, with a research focus on the influence of asatidz coaching on the morals of students, pondok said that there were still many students who had not/did not apply their adab. The purpose of this research is to find out how the influence of asatidz coaching has on the morals of students at the Sekolah Dasar Negeri 1. This is important to examine considering how far the asatidz guidance is on the morals of the students. The method used in this study is the correlation quantitative method and the Issac and Michael technique with a sample of 78 data from a population of 100 students. The theoretical analysis used for the coaching variable (X) is the theory from Syadam in Rudiana while the theory used for the moral variable (Y) is the theory from the book Taisiirul Khalaq Hafidz Hasan Al-Mas'udi. The research approach used includes descriptive correlational research because all the variables to be observed are described, then correlated between the independent variables and the dependent variable. The research method used by the author is a quantitative method. Based on the results of data analysis, it was concluded that first, asatidz coaching was considered very good with an average score of 84.04%. Second, the morals of the students were considered good with an average score of 64.99%. Third, there is an influence between asatidz coaching on the morals of students with a correlation value of 0.591 (medium correlation) which is significant at an alpha of 5%. Therefore the p-value is 0.591 > 0.05 so it can be concluded that there is an influence of asatidz coaching on the morals of the students